APLIKASI PUPUK HAYATI MAJEMUK CAIR PADA TANAMAN TEBU DI PT. PERKEBUNAN NUSANTARA X KEDIRI - Indah Kusumaning Putri; Zaenal Kusuma; Sugeng Prijono (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
The condition of increasing the demand for sugar is not balanced with the production of sugarcane because the production from year to year fluctuates. Continuous inorganic fertilization in sugar cane causes a decrease in soil productivity. This study that was aimed to determine the potential of biological fertilizer as a provider of soil nutrients to reduce the use of inorganic fertilizers for sugarcane was conducted at Sugar Research Center PT. Perkebunan Nusantara X Kediri. This study consisted of planting stage of sugarcane plant, application of liquid combined biofertilizer and observation of vegetative growth of sugar cane plant, and soil nutrient analysis. This study used a randomized block design using seven treatments with four replications. The treatments tested were P0 (without biofertilizer + without NPK fertilizer), P1 (100% NPK fertilizer), P2 (biological fertilizer + 100% NPK fertilizer), P3 (biological fertilizer + 75% NPK fertilizer), P4 (biological fertilizer + 50 % NPK fertilizer), P5 (biological fertilizer + 25% NPK fertilizer), P6 (biological fertilizer). The results indicated that the presence of bacteria could increase the growth of sugarcane and soil nutrients content. The best growth of sugarcane plantation occurred at the treatment of P2 (biological fertilizer + 100% NPK fertilizer).This was suspected to occur because the nutrient needs of the plant could be met quickly by the presence of inorganic fertilizers as well as the help of nitrogen fixing bacteria and phosphate solubilizing bacteria in the biological fertilizer.